Are Synonyms Always Synonymous? A Corpus-assisted Approach to Announce, Declare, and State - Ike Susanti Effendi; Riska Amalia; Sakinah Asa Lalita (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2020)
The study on (near) synonymous word has been of intriguing topic in the recent decades. Scholars have investigated them from diverse perspectives including but not limited to semantics, grammar, and language teaching. However, few of them examine synonymous verbs. This study endeavors to scrutinize ‘announce’, ‘declare’, and ‘state’ by employing descriptive qualitative approach and British National Corpus as data source. Besides, it also attempts to shed pivotal light the pedagogical implication of corpus linguistics to the teaching of word or vocabulary and meaning in use. Sketch Engine is used as instrument analysis by which collocation and concordance analysis were employed to elucidate word combination and contexts to produce meaning. The findings demonstrate that ‘announce’, ‘declare’, and ‘state’ could not be used rudimentary interchangeably since they carry out (slightly) different meaning depending on collocate word and grammatical pattern. This study also corroborated the notion that corpus linguistics plays significant role in foreign language teaching since it offers authentic materials and contextual clue for language use.